R. Buckminster Fuller on education - Fuller, R. Buckminster (University of Massachusetts Press, 1979)
Contents: Breaking the shell of permitted ignorance; Education automation: freeing scholars to return to their studies; Emergent humanity: it's environment and education; Hyper: a concept for an integrated physical education facility; Heartbeats in Illions; Science and humanities...